Difficulties of Biology Teachers in Planning and Implementing Authentic Assessments in the 2013 Curriculum: Descriptive Studies on Biology Teachers in Senior High Schools - Sholiha, Dwi Alviana; Ramdani, Agus; Merta, I Wayan (Prisma Sains : Jurnal Pengkajian Ilmu dan Pembelajaran Matematika dan IPA IKIP Mataram, 2021)
This study aims to describe the difficulties of biology teachers at senior high schools (SMA) in Praya Barat Daya District for the 2020/2021 academic year in planning and implementing an authentic assessment in the 2013 curriculum. This research method uses a descriptive qualitative approach. The informants in this study were biology teachers at SMAN 1 Praya Barat Daya, biology teachers at Al Maarif Pandan Indah Islamic High School, and biology teachers at Raudlatul Ulum Islamic High School Batu Jangkih, totaling 8 people. Data collection techniques are using questionnaires, interviews, and documentation. In analyzing the data, steps were applied, namely data reduction, exposure or presentation of data and drawing conclusions. The results showed that the process of implementing an authentic assessment carried out by biology teachers was still less effective. Obtained data in planning the assessment of 78.75% included in the good category and in the implementation of the assessment obtained data of 43.26% included in the poor category. The difficulties experienced by biology teachers in planning authentic assessments of the 2013 curriculum are in determining the standard of assessment and the difficulties experienced by teachers in carrying out authentic assessments are in the affective domain.